A Role for Transforming Growth Factor α as an Inducer of Astrogliosis - Rabchevsky, Alexander G. (J Neurosci, 1998)
TGFα is a member of the epidermal growth factor (EGF) family with which it shares the same receptor, the EGF receptor (EGFR). Synthesis of TGFα and EGFR in reactive astrocytes developing after CNS insults is associated with the differentiative and mitogenic effects of TGFα on cultured astrocytes. This suggests a role for TGFα in the development of astrogliosis. We evaluated this hypothesis using transgenic mice bearing the human TGFα cDNA under the control of the zinc-inducible metallothionein promoter. Expression levels of glial fibrillary acidic protein (GFAP) and vimentin and morphological features of astrocytes were used as indices of astroglial reactivity in adult transgenic versus wild-type mice provided with ZnCl(2)in their water for 3 weeks. In the striatum, the hippocampus, and the cervical spinal cord, the three CNS areas monitored, transgenic mice displayed enhanced GFAP mRNA and protein levels and elevated vimentin protein levels. GFAP-immunoreactive astrocytes exhibited numerous thick processes and hypertrophied somata, which are characteristic aspects of reactive astrocytes. Their number increased additionally in the striatum and the spinal cord, but no astrocytic proliferation was observed using bromodeoxyuridine immunohistochemistry. Neither the morphology nor the number of microglial cells appeared modified. A twofold increase in phosphorylated EGFR was detected in the striatum and was associated with the immunohistochemical detection of numerous GFAP-positive astrocytes bearing the EGFR, suggesting a direct action of TGFα on astrocytes. Altogether, these results demonstrate that enhanced TGFα synthesis is sufficient to trigger astrogliosis throughout the CNS, whereas microglial metabolism is unaffected.